2013
DOI: 10.1007/s40435-013-0036-7
|View full text |Cite
|
Sign up to set email alerts
|

Independent modal resonant shunt for multimode vibration control of a truss-cored sandwich panel

Abstract: To realize multimode vibration control of a trusscored sandwich panel, an independent modal resonant shunt control method is proposed in this paper. In this method, each piezoelectric stack transducer is connected to a single resonant shunt which is tuned to control the vibration of a single mode, and the location of the transducer is optimized to get a maximal electromechanical coupling with this mode. It is found that the optimal values of the resistance and inductance can not be determined by using a single… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Wu [75] proposed the parallel RL shunt circuit shown in Figure 4c, the similar shunt can be found in [76][77][78]. Guo and Jiang [79] utilized the R-L shunt to construct a modal piezoelectric transducer to control vibrations of a truss-cored sandwich panel. The series and parallel resonant shunts can obtain similar vibration control performance, but the parallel one is less sensitive to the optimal resistance.…”
Section: Single Modal Vibration Controlmentioning
confidence: 99%
“…Wu [75] proposed the parallel RL shunt circuit shown in Figure 4c, the similar shunt can be found in [76][77][78]. Guo and Jiang [79] utilized the R-L shunt to construct a modal piezoelectric transducer to control vibrations of a truss-cored sandwich panel. The series and parallel resonant shunts can obtain similar vibration control performance, but the parallel one is less sensitive to the optimal resistance.…”
Section: Single Modal Vibration Controlmentioning
confidence: 99%
“…But these tuning methods were based on one degree-of-freedom (DOF) systems. In [15] it is shown that when the number of mechanical DOF is far greater than the electrical DOF, the optimal RL value based on single-mode truncation can lose effectiveness, so a full-order model must be used in the optimization process. In the independent modal resonant shunt circuit method, supposing there are n modes to control, owing to the independence between the shunts, the 2n-dimensional optimization problem can be reduced to 2n one-dimensional problems while each can be resolved by a simple heuristic search method summarized below:…”
Section: Independent Modal Resonant Shunt Circuitmentioning
confidence: 99%
“…In these kinds of methods, in order to realize frequency selection of different modes, a large number of capacitances and inductances must be employed, which increases the complexity of the shunts. Thus, a kind of independent modal resonant shunt was proposed in [15]. In this method, a single mode is controlled using a single transducer and a single shunt circuit.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the controllable and varied physical properties of smart materials, they are also used for living infrastructures, mechanical structures, and seismic vibration controls for decades . Smart materials and structures that possess electromechanical characteristics have been widely used for active vibration control or semi-active vibration control, such as piezoelectric damper [4][5][6][7][8], eddy current damper [9], magnetostrictive spring [10], magneto-rheological fluid (MRF) damper [11][12][13], electro-rheological fluid (ERF) damper [14][15][16][17], shape memory alloy (SMA) [18][19][20][21], and electromagnetic and piezoelectric shunt damper [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Smart materials have one or more properties changed by the external stimuli, such as temperature, stress, electric field or magnetic field.…”
Section: Introductionmentioning
confidence: 99%